Konsep Pendidikan Anak dalam Islam Menurut Ibnu Qayyim Al-Jauziyah - Khoir, Mulyanto Abdullah; Luthfi, Moh; Azis, Muhamad Abdul (Lembaga Yasin AlSys, 2025)
This study aims to explore the concept of child education in Islam according to the perspective of Ibn Qayyim Al-Jauziyyah. The research method employed is descriptive qualitative with a library research approach. Data were collected through an analysis of Ibn Qayyim's primary works, such as Tuhfatul Maudud bi Ahkam al-Maulud, as well as relevant secondary literature. The study found that child education according to Ibn Qayyim Al-Jauziyyah involves several methods: the Habit Formation Method, the Exemplary Method, the Advisory Method, the Punishment Method, and the Learning by Doing Method. The results of this study provide a theoretical contribution to understanding the concept of child education from an Islamic perspective, particularly classical views, which are relevant for application in a modern context.